A Multilinguistic Spelling Analysis of Children who are Hard of Hearing. (18th September 2020) - Quick, Nancy A; Harrison, Melody; Erickson, Karen
Abstract: Spelling in writing samples was compared between children who are hard of hearing (HH) ( n = 142) and their peers with typical hearing (TH) ( n = 72) in second and fourth grade. The same analyses were then conducted comparing groups of children who are HH with different levels of aided audibility. Compared to children with TH, children who are HH produced fewer misspelled words ( p = .041, d = .42) at second grade but performed similarly in fourth grade (p = .943, d = .02). Compared to peers with TH, children who are HH demonstrated similar distributions of errors in roots but some differences in the distribution of errors for affixes. Different levels of aided audibility among children who are HH were not associated with significant differences in spelling accuracy at both grades. However, second-grade children with poorer aided audibility produced significantly more phonological omissions ( p = .005, r = .32) and orthographic consonant errors for monomorphemic words ( p = .001, r = .37), as well as more orthographic consonant errors for and affixes ( p = .015, r = .28).